The Influence of Father Involvement, Self-Esteem, and Social Skills on Bullying Behavior Among University Students - Chr. Argo Widiharto; Arri Handayani; Desi Maulia (Grief and Trauma, 2026)
Bullying remains a significant problem in higher education and may negatively affect students’ psychological and social well-being. This study aimed to examine the simultaneous and partial effects of father involvement, self-esteem, and social skills on bullying behavior among university students. The study employed a quantitative correlational design using a cross-sectional survey approach. Participants consisted of 289 university students from 18 cities in Central Java, Indonesia. Data were collected using the Bullying Scale, Inventory of Father Involvement (IFI), Self-Esteem Scale, and Social Skills Scale. Data were analyzed using descriptive statistics, multiple regression analysis, and path analysis with the assistance of IBM SPSS Statistics 25. The results showed that father involvement, self-esteem, and social skills simultaneously had a significant effect on bullying behavior, explaining 46.4% of the variance. Social skills emerged as the strongest predictor, followed by self-esteem and father involvement. All variables showed significant negative relationships with bullying behavior, indicating that higher levels of father involvement, self-esteem, and social skills were associated with lower bullying behavior. In addition, father involvement was categorized as high, while self-esteem, social skills, and bullying behavior were generally in the moderate category. These findings suggest that bullying behavior among university students is influenced by both psychological and family-related factors. Therefore, bullying prevention programs should emphasize the development of social skills, enhancement of self-esteem, and strengthening of parental involvement, particularly father involvement, within higher education settings.